Role of Reactive Oxygen Species in Collagen-Induced Platelet Activation and the Protective Effects of Antioxidants - Jin-Yi Han; Hideo Utsumi; Han-Young Chung (Antioxidants)
Collagen plays a crucial role in platelet activation and thrombosis, yet the underlying mechanisms involving reactive oxygen species (ROS) remain incompletely understood. This study investigated how collagen modulates ROS generation and platelet aggregation both in vitro and in vivo, as well as evaluating the protective effects of antioxidants. In vitro, collagen induced dose-dependent platelet aggregation and increased ROS generation, evidenced by the enhanced EMPO adduct formation detected via electron spin resonance (ESR). In vivo experiments demonstrated that collagen administration significantly accelerated CAT-1 decay, indicating elevated oxidative stress with a transient peak around 1 minute post-treatment. Furthermore, escalating collagen doses correlated with increased ROS generation and reduced survival rates in mice, underscoring collagen’s impact on oxidative stress and thrombosis severity. Importantly, treatment with enzymatic antioxidants (superoxide dismutase, catalase) and non-enzymatic antioxidants (DMTU, Tiron, mannitol) significantly attenuated collagen-induced oxidative stress and improved animal survival. Collectively, these findings elucidate the pivotal role of ROS in collagen-induced platelet activation and thrombosis and highlight antioxidants as promising therapeutic candidates for preventing thrombotic disorders and managing cardiovascular risk.